Case report: Rhabdomyolysis and kidney injury in a statin-treated hypothyroid patient–kill two birds with one stone - Chiang, Wen-Fang; Chan, Jenq-Shyong; Hsiao, Po-Jen; Lin, Shih-Hua (Frontiers in Medicine, 2022)
Statin treatment for hypercholesterolemia may cause reversible rhabdomyolysis and acute kidney injury in susceptible patients. However, persistent rhabdomyolysis and acute kidney injury following discontinuation of statins require careful evaluation of the underlying causes to avoid missing a curable disease. We describe a 50-year-old woman with hypercholesterolemia [total cholesterol 345 mg/dl, low-density lipoprotein cholesterol (LDL-C) 266 mg/dL] on atorvastatin therapy (40 mg daily) for 1 month that presented with myalgia and muscle weakness. Relevant laboratory studies revealed persistent higher hypercholesterolemia with total cholesterol (312 mg/dL), high creatine kinase (CK) (5,178 U/L), and high creatinine levels (1.5 mg/dL) without dysmorphic red blood cells and proteinuria. Despite the cessation of statin therapy, serum CK level increased to 9,594 U/L, and creatinine remained at 1.5 mg/dL. A thorough work-up to assess potential underlying causes indicated low T3 and free T4 and high thyroid-stimulating hormone (TSH) levels, consistent with hypothyroidism. With aggressive thyroxine replacement for 1 month, all of the clinical features, along with elevated serum CK and creatinine levels, were completely resolved. This case highlights the fact that hypothyroidism must be kept in mind as a potential cause of concomitant myopathy and kidney injury, especially in patients with statin-resistant hypercholesterolemia.